Approach for filtering crossover design using mixed electric and magnetic coupling. Issue 9 (1st May 2018) - Luo, Ming; Tang, Xiao‐Hong; Lu, Di; Zhang, Yong‐Hong
Abstract : A new approach for the filtering crossover design is proposed in this Letter. This approach is based on the mixed electric and magnetic coupling. A compact filtering crossover constructed by the short stub loaded resonator is presented according to the proposed approach. By using a short stub loaded resonator the filtering response is achieved and by using the cancelling effect between the electric coupling and magnetic coupling, the isolation between two signal paths is achieved. A filtering crossover is fabricated for demonstration. The measured result presents good agreement with the simulated result.